Inlay Patellofemoral Arthroplasty: A Readily Reproducible Technique - Mario Hevesi MD, PhD; Elyse J. Berlinberg BS; Harsh H. Patel BA; Pablo Ramos MD; Brian Forsythe MD (SAGE Publishing, 2022)
Background: Patients with recalcitrant anterior knee pain and isolated patellofemoral osteoarthritis (PFOA) may benefit from patellofemoral arthroplasty. Arthroplasty with an inlay implant may be beneficial given recreation of native biomechanics and potentially avoiding anterior overstuffing. Indications: Patellofemoral arthroplasty is indicated in patients with anterior knee pain from isolated PFOA in patients with neutral alignment and intact menisci and ligaments. To highlight these indications, we present a 32-year-old female with severe anterior knee pain from PFOA, not resolved by conservative measures. Preoperative imaging demonstrated full-thickness chondral loss of the lateral patellar facet and trochlea, with neutral alignment and no significant trochlear dysplasia. Technique Description: This technique utilized the HemiCap Wave Implant manufactured by Anika Therapeutics (Franklin, MA, USA). A standard midline approach and medial parapatellar arthrotomy is performed. The patella is everted, and the trochlea is exposed. A guide pin is placed perpendicular to the trochlear bony surface and centrally in the defect. The pin is advanced, and the surrounding area is reamed. A guide block is placed over the pin in the trochlea and over-reamed. The area is prepared and centrally drilled, then tapped. A taper post is implanted. The trochlear implant is then secured to the taper post with an impactor and mallet. On the patellar side, a guide pin is placed in the center of the patella. Consideration is given to medialization of the button to decrease Q-angle. The patella is reamed to the diameter of an appropriately sized patellar button. A trial button is used to ensure satisfactory tracking. A real patellar implant is then cemented into place. Standard closure is performed. Results: Overall outcomes following inlay patellofemoral arthroplasty have been positive, with up to 89% of patients engaging in sports at 2 years status post surgery and 83% survival free of total knee arthroplasty at 5 years postoperatively. Discussion/Conclusion: Patellofemoral arthroplasty can provide good satisfaction and high rates of return to sport in patients with symptomatic, isolated patellofemoral arthritis. The surgical technique video presented provides reproducible steps, tips, and tricks for performing this procedure.